EFFECTS OF METHYL JASMONATE AND CADMIUM ON GROWTH TRAITS, CADMIUM TRANSPORT AND ACCUMULATION, AND ALLENE-OXIDE CYCLASE GENE EXPRESSION IN WHEAT SEEDLINGS - Ozra Alikhani; Hossein Abbaspour (Revista de Agricultura Neotropical, 2019)
This research investigated the toxicity effects of cadmium chloride (0, 100, 200 and 300 μM) and its interactive effects with methyl jasmonate (MeJA) (0, 0.01 and 0.1 mM) on growth parameters, cadmium (Cd) accumulation, and Allene-Oxide Cyclase (AOC) gene expression in wheat seedling (Sivand cultivar). According to the results, Cd at concentrations of 200 μM and 300 μM reduced the growth traits of the wheat. Under exposure to 300 μM Cd, root and shoot cadmium content was 30 and 17 times greater than the base level, respectively. Under 100 μM Cd exposures, bioaccumulation factor (BCF) for root and shoot increased by 46 and 25 times respectively. The spraying of MeJA on Cd-stressed plants showed a positive effect on growth parameters, increasing them by 10-40%. The treatment with 0.01 mM  jasmonate decreased the accumulation of cadmium in root and shoot by about 30%. The same amount of decrease was observed in BCF after the jasmonate treatment of the specimens exposed to Cd. But application of 0.1 MeJA increased the BCF in most Cd concentrations. Under exposure to 200 μM Cd, AOC expression showed an approximately three fold increase. The use of 0.1 mM MeJA also resulted in a fourfold increase in AOC gene expression. It can conclude that MeJA showed a substantial impact on Cd accumulation and AOC gene expression in wheat seedling.